Sitagliptin protects rat kidneys from acute ischemia-reperfusion injury via upregulation of GLP-1 and GLP-1 receptors - Chang Meng-wei; Chen Chih-hung; Chen Yi-ching; Wu Ying-chun; Zhen Yen-yi; Leu Steve; Tsai Tzu-hsien; Ko Sheung-fat; Sung Pei-hsun; Yang Chih-chau; Chiang Hsin-ju; Chang Hsueh-wen; et al. (Acta Pharmacologica Sinica, 2017)
Aim: Sitagliptin, an oral glucose-lowering agent, has been found to produce cardiovascular protection possibly via anti-inflammatory and anti-atherosclerotic activities of glucagon-like peptide-1 receptor (GLP-1). The aim of this study was to investigate whether sitagliptin protected the kidney function from acute ischemia-reperfusion (IR) injury in rats. Methods: Adult male SD rats were categorized into 4 groups: sham control, IR injury, IR+sitagliptin (300 mg/kg) and IR+sitagliptin (600 mg/kg). Acute renal IR injury of both kidneys was induced by clamping the renal pedicles for 1 h. The drug was orally administered at 1, 24 and 48 h after acute IR. Blood samples and 24-h urine were collected before and at 72 h after acute IR. Then the rats were sacrificed, and the kidneys were harvested for biochemical and immunohistochemical studies. Results: Acute IR procedure markedly increased serum levels of creatinine and BUN and the ratio of urine protein to creatinine. The kidney injury score, inflammatory biomarkers (MMP-9, TNF-α and NF-κB) levels and CD68+ cells in IR kidneys were considerably increased. The expression of oxidized protein, reactive oxygen species (NOX-1, NOX-2) and apoptosis proteins (Bax, caspase-3, PARP) in IR kidneys was also significantly upregulated. All these pathological changes were suppressed by sitagliptin in a dose-dependent manner. Furthermore, the serum GLP-1 level, and the expression of GLP-1 receptor, anti-oxidant biomarkers (HO-1 and NQO-1 cells, as well as SOD-1, NQO-1 and HO-1 proteins), and angiogenesis markers (SDF-1α+ and CXCR4+ cells) in IR kidneys were significantly increased, and further upregulated by sitagliptin. Conclusion: Sitagliptin dose-dependently protects rat kidneys from acute IR injury via upregulation of serum GLP-1 and GLP-1 receptor expression in kidneys.